2013
DOI: 10.1099/mic.0.070755-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of extracellular surface-layer associated proteins in Lactobacillus acidophilus NCFM

Abstract: Bacterial surface (S-) layers are crystalline arrays of self-assembling, proteinaceous subunits called S-layer proteins (Slps), with molecular masses ranging from 40 to 200 kDa. The S-layer-forming bacterium Lactobacillus acidophilus NCFM expresses three major Slps: SlpA (46 kDa), SlpB (47 kDa) and SlpX (51 kDa). SlpA has a demonstrated role in adhesion to Caco-2 intestinal epithelial cells in vitro, and has been shown to modulate dendritic cell (DC) and T-cell functionalities with murine DCs. In this study, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(138 citation statements)
references
References 64 publications
4
131
0
Order By: Relevance
“…During this work, we identified the main actors explaining this phenotype. Thus, as has been demonstrated for lactobacilli and bifidobacteria2634, the immunomodulatory response is the result of the detection by immunocompetent cells of a mosaic of surface proteins and other components (pro-and anti-inflammatory proteins). All these components contribute to the net balance of immunomodulatory properties of Pf strains.…”
Section: Discussionmentioning
confidence: 92%
“…During this work, we identified the main actors explaining this phenotype. Thus, as has been demonstrated for lactobacilli and bifidobacteria2634, the immunomodulatory response is the result of the detection by immunocompetent cells of a mosaic of surface proteins and other components (pro-and anti-inflammatory proteins). All these components contribute to the net balance of immunomodulatory properties of Pf strains.…”
Section: Discussionmentioning
confidence: 92%
“…The SLPs of L. acidophilus fb11 also contributed positively to the probiotic activities of strains (data not shown). Johnson et al [4] identified 37 surface-layer associated proteins from L. acidophilus NCFM by lithium chloride extraction, including three major SLPs: SlpA (46 kDa), SlpB (47 kDa) and SlpX (51 kDa). In this study, the major lytic band was 46 kDa.…”
Section: Zymogram Of the Slps From The Two L Acidophilus Strainsmentioning
confidence: 99%
“…Many species of the genus Lactobacillus have been found to possess SLPs [3] and the structures and functions of those of L. acidophilus strains have been investigated extensively. Johnson et al [4] reported a modified method to extract the surface-layer associated proteins of L. acidophilus NCFM using lithium chloride that revealed 37 proteins, some of which might be loosely associated with or embedded within the bacterial surface layer complex and appeared to contribute considerably to the immunological properties and surface display features of the microbes.…”
Section: Introductionmentioning
confidence: 99%
“…None of the 3 proteins, previously thought to be composed of a 630 single protein molecular species, are more complex in631 Gram-positive bacteria such as L. acidophilus, the S-layer of 632 which contains 37 proteins[61], in addition to the previously 633 described SlpA. In P. freudenreichii ITG P20, at least 5 proteins634 are extracted using guanidine, SlpB being the major one, with 635 a MS-measured mass of 54,147 Da, which is close to the 636 54,145 Da size predicted for SlpB after cleavage of the signal 637 peptide (this work, predicted from the slpB gene).…”
mentioning
confidence: 99%